2013
DOI: 10.4172/2167-1206.1000133
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Activities of Turmeric (Curcuma longa linn): A Review

Abstract: Apsmar denotes epilepsy, that usually persists in majority of patients with mental debility and disability, in spite of multidrug therapy with advanced anti-epileptics. But by supplementing Sodium valproate with indigenous composite of some Indian herbs as an adjuvant at 8 hourly dosing, tends to modulate the therapeutic outcome positively due to bioregulation of altered GABA bio kinetics and neurogenic action. Thus this adjunction seems a boon in epilepsy management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(81 citation statements)
references
References 28 publications
2
70
0
9
Order By: Relevance
“…Similarly, Tilak et al [26] reported a TFC of turmeric from India ranging from 3.58 to 7.86 mg/g of turmeric. Polyphenols including flavonoids are extensively investigated in turmeric for their wide range of pharmacological activities [27]. Flavonoids are the antioxidants that can prevent or delay the oxidation of substrates even when it is present in low concentrations, so as to prevent oxidation by the prooxidants (ROS and RNS).…”
Section: Flavonoid Contentmentioning
confidence: 99%
“…Similarly, Tilak et al [26] reported a TFC of turmeric from India ranging from 3.58 to 7.86 mg/g of turmeric. Polyphenols including flavonoids are extensively investigated in turmeric for their wide range of pharmacological activities [27]. Flavonoids are the antioxidants that can prevent or delay the oxidation of substrates even when it is present in low concentrations, so as to prevent oxidation by the prooxidants (ROS and RNS).…”
Section: Flavonoid Contentmentioning
confidence: 99%
“…In a recent study of atherosclerosis, curcumin treated mice which were fed with atherogenic diet after four months showed a 20% decrease in blockage of arteries than mice fed without curcumin. [13] Cardioprotective activity…”
Section: Hypolipidemic Activitymentioning
confidence: 99%
“…Combined treatment of curcumin and gingermaximize the protection of liver from injury and fibrogenesis due to CCl4 intoxication.curcumin and ginger returned collagen fiber distribution to almost normal pattern. [12][13][14][15][16][17] …”
Section: ] [6]mentioning
confidence: 99%